2021
DOI: 10.3389/fpls.2021.708233
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection in Sugarcane: Current Status and Future Prospects

Abstract: Sugarcane is a C4 and agro-industry-based crop with a high potential for biomass production. It serves as raw material for the production of sugar, ethanol, and electricity. Modern sugarcane varieties are derived from the interspecific and intergeneric hybridization between Saccharum officinarum, Saccharum spontaneum, and other wild relatives. Sugarcane breeding programmes are broadly categorized into germplasm collection and characterization, pre-breeding and genetic base-broadening, and varietal development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 198 publications
(342 reference statements)
0
7
0
Order By: Relevance
“…The relationship between yield (Y) and stalk number (SN), stalk height (SH), and stalk weight (SW) has also been reported by Barreto et al [ 5 ] and Yang et al [ 14 ]. In addition, evidence from genetics also showed that both yield and sucrose were governed by many quantitative trait loci (QTL) or genomic regions [ 14 , 39 ]. These studies also revealed the complexity of high-yield sugarcane breeding and high-sucrose yield breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between yield (Y) and stalk number (SN), stalk height (SH), and stalk weight (SW) has also been reported by Barreto et al [ 5 ] and Yang et al [ 14 ]. In addition, evidence from genetics also showed that both yield and sucrose were governed by many quantitative trait loci (QTL) or genomic regions [ 14 , 39 ]. These studies also revealed the complexity of high-yield sugarcane breeding and high-sucrose yield breeding.…”
Section: Discussionmentioning
confidence: 99%
“…S. spontaneum L., a wild material, is gathered in a single cluster, whereas cultivar materials are distributed among different communities. In the long-term domestic and breeding process, the genetic background of different wild accessions is introduced to the genome of cultivated species [ 60 ]. These sugarcane germplasm exchanges led to an indistinct correlation between the results of population genetic analysis and geographical origin.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic gain for these traits through phenotypic selection is very low. This is because the accumulation of superior alleles for these traits via phenotypic breeding value is very rare ( Jackson, 2005 ; Mahadevaiah et al, 2021 ). Therefore, it is only possible to accumulate favorable alleles for these traits through recurrent selection schemes ( Lingle et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additive genetic variance is a proportion of genetic variance inherited in progeny, which is helpful in the selection of desired parental combinations. Non-additive variance, on the other hand, is helpful in the selection of desired plant types during selection from the ground nursery ( Jackson et al, 2016 ; Mahadevaiah et al, 2021 ). As cane yield is reflected by low narrow-sense heritability and CCS has a moderate level of heritability, also governed polygenically ( Hoang et al, 2015 ), both non-additive and additive effects must be taken into account to improve the overall performance of these traits.…”
Section: Introductionmentioning
confidence: 99%